Endothelial plasticity across PTEN and Hippo pathways: A complex hormetic rheostat modulated by extracellular vesicles (2023)
ABSTRACT: Vascularization is a multifactorial and spatiotemporally regulated process, essential for cell and tissue survival. Vascular alterations have repercussions on the development and progression of diseases such as cancer, cardiovascular diseases, and diabetes, which are the leading causes of death worldwide. Additionally, vascularization continues to be a challenge for tissue engineering and regenerative medicine. Hence, vascularization is the center of interest for physiology, pathophysiology, and therapeutic processes. Within vascularization, phosphatase and tensin homolog deleted on chromosome 10 (PTEN) and Hippo signaling have pivotal roles in the development and homeostasis of the vascular system. Their suppression is related to several pathologies, including developmental defects and cancer. Non-coding RNAs (ncRNAs) are among the regulators of PTEN and/or Hippo pathways during development and disease. The purpose of this paper is to review and discuss the mechanisms by which exosome-derived ncRNAs modulate endothelial cell plasticity during physiological and pathological angiogenesis, through the regulation of PTEN and Hippo pathways, aiming to establish new perspectives on cellular communication during tumoral and regenerative vascularization.